Assessment of crop loss caused by Chilo partellus in maize - KUMAR, PRADYUMN; B, SUBY S; JASWINDER, KAUR; R, BAJYA D; C, SEKHAR J; LAKSHMI, SOUJANYA P; JAWALA, JINDAL; RANVIR, SINGH; K, BANA J; M, REDDY L; JHA, GIRISH K (The Indian Journal of Agricultural Sciences, 2021)
The crop loss assessment in the present study is based on the premise that yield loss caused by maize stem borer, Chilo partellus (Swinhoe) depends upon the degree of leaf injury measured in the form of leaf injury rating (LIR) that would help in adopting management measures at appropriate time to prevent the loss. The yield of large number of individual plants in two popular maize hybrids, i.e. HQPM1 and DHM117 was recorded at all leaf injury ratings at ICAR-Indian Institute of Maize Research, Pusa Campus, New Delhi. With increasing LIR, the average yield of plants decreased. A set of formula was developed to calculate yield loss, yield loss percentage and monetary loss. A template to calculate the same was formulated in excel sheet by entering input data on LIR scores, average yield at LIR, frequency of plants under each LIR, yield potential of test cultivars and market price of maize grain. The template gives output on yield loss percentage due to C. partellus damage and the corresponding economic loss by entering frequency of plants under each LIR, yield potential of cultivar and the current market price of grain. By comparing economic loss with the management cost, the economic threshold level can be determined which is an essential prerequisite for robust integrated pest management. After the harvest, by deducting actual yield from the expected yield (C. partellus yield loss), the loss caused by other factors is also calculated by the template.